Isolasi dan Identifikasi Snyawa Geraniol dari Minyak Atsiri Tanaman Sereh Wangi Cymbopogon nardus (L.) Rendle - Yelfi Anwar; Shirly Kumala; Elvina Dhiaul Iftitah; Partomuan Simanjuntak (Fakultas Farmasi Universitas Pancasila, 2019)
Background: Indonesia is a major producer of several essential oils such as citronella oil, clove oil, cananga oil, vetiver oil, sandalwood oil, and patchouli oil. The Cymbopogon (Poaceae) genus has the most important components of essential oils, namely citral, geraniol, citronellol, citronellal. Geraniol is one of the most important chemical compounds in the aroma and fragrance industry and shows the nature of insecticides and natural insect repellents which show low toxicity and is suggested to represent a new class of chemoprevention agents for cancer, antimicrobial, anti-oxidant, anti-inflammatory and some vascular effects Transdermal drugs also attract the attention of researchers and scientists in the field of formulation. Objective: This study aimed to obtain geraniol compounds obtained from Cymbopogon nardus (L.) Rendle and identification. Methodology: The citronella, essential oil was obtained from the Cymbopogon nardus (L) Rendle plant using a water-steam distillation method, then fractionation was carried out and continued by purification isolation by column chromatography. Results: Based on the interpretation of IR data, Core magnetic resonance (proton and carbon RMI) and mass spectra for isolate 5 were determined as geraniol compounds. Conclusion: Geraniol can be obtained from Cymbopogon nardus (L) Rendle plants by water-steam distillation, fractionation and isolation methods.